Effects of Ovine Monocyte-Derived Macrophage Infection by Recently Isolated Toxoplasma gondii Strains Showing Different Phenotypic Traits - Raquel Vallejo; Julio Benavides; Noive Arteche-Villasol; Mercedes Fernández-Escobar; María Del Carmen Ferreras; Valentín Pérez; Daniel Gutiérrez-Expósito (Animals, 2022)
Ovine toxoplasmosis is one the most relevant reproductive diseases in sheep. The genetic variability among different Toxoplasma gondii isolates is known to be related to different degrees of virulence in mice and humans, but little is known regarding its potential effects in sheep. The aim of this study was to investigate the effect of genetic variability (types II (ToxoDB #1 and #3) and III (#2)) of six recently isolated strains that showed different phenotypic traits both in a normalized mouse model and in ovine trophoblasts, in ovine monocyte-derived macrophages and the subsequent transcript expression of cytokines and iNOS (inducible nitric oxide synthase). The type III isolate (TgShSp24) showed the highest rate of internalization, followed by the type II clonal isolate (TgShSp2), while the type II PRU isolates (TgShSp1, TgShSp3, TgShSp11 and TgShSp16) showed the lowest rates. The type II PRU strains, isolated from abortions, exhibited higher levels of anti-inflammatory cytokines and iNOS than those obtained from the myocardium of chronically infected sheep (type II PRU strains and type III), which had higher levels of pro-inflammatory cytokines. The present results show the existence of significant intra- and inter-genotypic differences in the parasite-macrophage relationship that need to be confirmed in in vivo experiments.